Ultrasonic Studies and Molecular Interactions of N, N-Dimethyl Formamide and 1-Butanol with n-Hexane at Different Temperatures 303K ,308K and 313K. - P.S., Syed Ibrahim; S, Chidambaravinayagam; J, Senthil Murugan; J, Edward Jeyakumar (International Research Journal of Multidisciplinary Technovation, 2019)
The Ultrasonic velocity(U), density(?), and viscosity(?) have been measured for the ternary liquid mixtures of N,N-Dimethyl Formamide (NNDMF), 1 butanol and n hexane at various temperatures viz., 303 k,308 k and 313 k at constant frequency 2 MHz. for different concentrations ranges from 0.001M to 0.01M. The acoustical parameters such as adiabatic compressibility(?), Rao constant(R), absorption coefficient (?/f2), internal pressure(?i), cohesive energy(CE), free volume(Vf), free length(Lf) and acoustic impedence(z), were calculated from the experimental data. These parameters in accordance with their ultrasonic velocities corresponding to different concentrations were discussed.